THERMAL INSULATION BOARDS FROM COCONUT PITH - RAO, C V. N.; PRABHU, P V; VENKATARAMAN, R (Fishery Technology, 2025)
Processing technique and physical characteristics of thermal insulation boards prepared from coconut pith using rubber latex as the binding agent are reported in this communication. In view of the easy processing, low cost and comparable physical properties with other insulating materials availble indigenously, manufacture of these boards appears to be promising,